What Does the Future Hold for U.S. Unionism? - Freeman, Richard (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 1989)
The author explores the reasons for the recent decline in U.S. private sector unionization and considers four possible scenarios of change in the future.